2011
DOI: 10.4102/jtscm.v5i1.78
|View full text |Cite
|
Sign up to set email alerts
|

The effect of problems on supply chain wide efficiency

Abstract: For any business to compete successfully in the modern, globalised business environment, it needs to mobilise its suppliers and customers to co-operate in order to reduce unnecessary costs and inefficiencies between them and to ensure the best value for the final customer. The focus is on management of the supply chain as a whole (or a system) and maximum value for the final customer of the supply chain, instead of on management for the maximum benefit of one of the parties in the supply chain. If the supply c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The major actors in the automotive industry comprise the OEMs, such as Toyota, Nissan, and Ford, and their suppliers, the ACMs. A survey among ACMs to determine the nature of the relationships that exist between buyers and suppliers in South Africa’s automotive supply chains showed that, while collaborative relationships do indeed exist between members of the supply chain, this relationship can be improved by communication, understanding of the parties’ situations and cooperation; in this way an alliance between OEMs and ACMs can be created (Naude and Badenhorst-Weiss, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The major actors in the automotive industry comprise the OEMs, such as Toyota, Nissan, and Ford, and their suppliers, the ACMs. A survey among ACMs to determine the nature of the relationships that exist between buyers and suppliers in South Africa’s automotive supply chains showed that, while collaborative relationships do indeed exist between members of the supply chain, this relationship can be improved by communication, understanding of the parties’ situations and cooperation; in this way an alliance between OEMs and ACMs can be created (Naude and Badenhorst-Weiss, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The challenges faced were broadly classified into technological, infrastructure, cost, market/service, relationship and production/skills challenges by Ambe (2014), who also suggested that, if these challenges were addressed, the sector could become globally competitive. Naude and Badenhorst-Weiss (2011) identified certain weaknesses in South African automotive industry’s supply chains. Although collaborative relationships exist, a better understanding of the parties’ situations could improve this relationship and create a stronger alliance between OEMs and ACMs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Many manufacturing business organizations are using information and communication technology (ICT) in there all supply chain management activities (Naude & Badenhorst-Weiss, 2011). ICT is the latest technological concept defined as an extensive method.…”
Section: Information System Managementmentioning
confidence: 99%